Islamic Counseling Interventions for Strengthening Family Bonds: Voices from Muslim Parents - Nina Siti Marlina (Islamic Counseling and Parenting Journal, 2025)
The stability and cohesion of family structures within Muslim communities are increasingly challenged by modern societal changes, including globalization, shifting gender roles, and declining religious engagement. Islamic counseling, which integrates spiritual and cultural values rooted in the Qur'an and Hadith, offers a potentially effective framework to reinforce familial bonds. This study explores the lived experiences of Muslim parents who have participated in Islamic counseling interventions aimed at strengthening family relationships. Using a qualitative descriptive method grounded in a phenomenological approach, data were collected from 12 Muslim parents in urban Indonesia through semi-structured interviews. Thematic analysis revealed four key outcomes of Islamic counseling: (1) the effective integration of Islamic teachings in therapy sessions, (2) improved communication within the family, (3) clarification and strengthening of parental roles, and (4) enhanced emotional and spiritual cohesion. These outcomes reflect a significant alignment between religious values and therapeutic techniques, offering a culturally congruent pathway to resolve family conflicts and reinforce unity. The findings align with previous studies emphasizing the relevance of culturally sensitive counseling practices, while also revealing new insights into clients’ perspectives. The study has important implications for counselors, educators, and policymakers in Muslim-majority contexts, suggesting the need for developing standardized, faith-based counseling models and expanding counselor training programs to include Islamic psychological frameworks. Future research should include diverse demographics and employ longitudinal methods to assess long-term impact.